Implementasi Lesson Study Terhadap Aktivitas Belajar Mahasiswa Fisika Berdasarkan Pendekatan Kontruktivistik - Irawan, Ferry; Akbar, Muh. Nur; Hanip, Rival (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The lack of experience in Lesson Study makes professionalism, especially in pedagogical competence, less improved. The lack of implementation of LS makes collaboration between teachers in determining innovative learning and reflection to improve the quality of the learning process becomes less, so that it has an impact on student activities. The purposes of this study are: (1) to find out student learning activities through the application of Lesson Study and (2) to train students to transform their knowledge as prospective teaching staff. The data taken from this study are (1) data on the implementation of LS activities with the application of the Jigsaw cooperative learning model, (2) data on the implementation of LS activities with the application of the STAD type cooperative learning model combined with Snowball Throwing, (3) data on student learning activities and (4) data on the results of reflection on the application of Lesson Study. The results of the study show that student activities can be well reflected in the implementation of Lesson Study and the implementation of LS in the learning process can also provide understanding to prospective educators on pedagogic competence.